Pengaruh Kepuasan Komunikasi Bawahan Dan Kompetensi Komunikasi Atasan Terhadap Kinerja Pegawai (Studi Pada Yayasan Mitra Sauri Utama Medan) - Setiamenda Ginting; Evi Enitari Napitupulu; Noyanta Luga; Merliana Laia; Elwin Famaugu (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2022)
This research tries to test several factors that are theoretically thought to have an influence on employee performance, namely subordinate communication satisfaction and superior communication competence. The research questions asked in this study are the influence of subordinate communication satisfaction on employee performance, the influence of superior communication competence on employee performance, the influence of subordinate communication satisfaction and superior communication competence on employee performance, what are the dominant factors that shape subordinate communication satisfaction, superior communication competence and performance employee at the Mitra Sauri Utama Foundation, Medan. This research found several important conclusions that all hypotheses in this research were not proven significantly. Second, the dominant factors that shape communication satisfaction, communication competence and employee performance at the Mitra Sauri Utama Foundation in Medan are communication climate, ability to decode messages and quantity of work output, respectively.